Ґрунтові некрополі лісостепового населення скіфської доби у Дніпровському Лівобережжі - Супруненко, О.Б. (Археологія і давня історія України, 2016)
Про нещодавно відкриті ґрунтові могильники
скіфського часу на Полтавщині. Публикуются комплексы недавно открытых грунтовых могильников лесостепного населения скифского времени VII—IV вв. до н. э. в бассейнах Ворсклы
и Псла на Полтавщине, в частности, в урочищах Перещепино и «Поле 2-й бригады» у с. Бельск Котелевского района, по ул. Шевченко в с. Дучинцы Гадячского района и в г. Полтава, по ул. Комсомольской,
22. Находки подтверждают, что грунтовые некрополи были основным типом погребальных памятников
в среде населения многочисленных лесостепных селищ и городищ Левобережья Днепра скифской эпохи раннего железного века. The paper deals with the Scythian epoch burial
grounds — dated back to 7th—4st centuries BC — of the
Forest-Steppe population that were recently discovered
in the basins of rivers Vorskla and Psel, Poltava
region: in particular, these are the Pereschepyno tract
and «Pole 2-yi bryhady» (the «Field of the Second Brigade
») near the village Bel’sk, Kotel’va district, and
also on Shevchenko street in the village Duchyntsy
in Hadiach district, as well as in Komsomolskaya street, 22, in Poltava. The author maintains an idea
that burial grounds were the major type of burial sites among the population of many forest-steppe tracts and
settlements in the Dnieper Left Bank Area during the Scythian epoch in the early Iron Age.